Effect of temperature, humidity and photoperiod on mortality of Mononychellus tanajoa (Acari: tetranychidae) infected by Neozygites cf. floridana (Zygomycetes: entomophthorales) - Oduor, G.I.; Moraes, G.J. de; Yaninek, John S.; Geest, L.P. van der (1995)
The effect of temperature, humidity and photoperiod on the development of Neozygites cf. floridana (Weiser and Muma) in the cassava green mite, Mononychellus tanajoa (Bondar) was studied in the laboratory. Dead infected mites began to appear 2.5 days after inoculation. At 33 and 28°C peak mortalities were higher and occurred earlier (after 2.5 days), than at 23 and 18°C. Mean LT50 (time for half the infected mites to die) decreased with increasing temperature as follows: 3.9, 3.0, 2.9 and 2.5 days at 18, 23, 28 and 33°C, respectively. When placed under conditions of high relative humidity for a period of 24 h, the percentage of dead infected mites from which the fungus sporulated was highest at 28°C (51.4%) and lowest at 33°C (6.5%). The development of the fungus inside the mite was not significantly affected by ambient humidity or photoperiod. No significant interactions between tested factors were found.